Estimation of the Nitrite Concentration in the Raw Milk and Locally Produced Soft Cheese in Different Area of Baghdad, Iraq - Mahdi Abed Rabba Al-Shuwaili; Zina Saab Khudhir (مجلة الانبار للعلوم البيطرية)
Samples for both raw milk and locally produced soft cheese totally (150), 75 for each were collected from different regions of Baghdad from October 2020 to July 2021 to estimate nitrite concentration. Ion exchange chromatography was used to detect the nitrite levels in the samples. The Limit of Detection (LOD) and Limit of Quantification (LOQ) were 0.5 mg/L and 1.7 mg/L respectively. The levels of nitrite in the samples of raw milk were (0.5-1.5 mg/L) with average (0.9 ± 0.4 mg/L), while the concentrations were (0.8-2.3 g/kg) in the soft cheese samples with average (1.4 ± 0.4 g/kg). The nitrite level in the soft cheese was higher than in the raw milk according to the months significantly (P<0.05). The presence of nitrite in milk and cheese indicates a poorness of hygiene practices during milking and post-milking operations, as well as during cheese production.